Microservice architecture in E-learning - Milovanović, Ana (E-business technologies conference proceedings, 2021)
Microservice architecture has found its application in the design and implementation of systems used in e-learning. Multiple cases of applying microservice architecture in e-education were considered and it is determined that there is a place to further investigate integration of the custom e-learning microservices with some existing LMS (Learning Management System) such as Moodle LMS. The aim of this paper is to present a possible solution of a custom microservice architecture that is based on integration with some existing LMS. The approach that was used to identify microservices is Domain Driven Design. Integration of the Cloud Data Platform into this architecture is also considered.